2005
DOI: 10.1037/0893-164x.19.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Do daily interactive voice response reports of smoking behavior correspond with retrospective reports?

Abstract: This study focuses on comparing reports of cigarette consumption using an interactive voice response (IVR) system and the timeline follow-back (TLFB) method. As part of a smoking cessation trial, daily reports of cigarette use were collected using an IVR system and TLFB for 7 days after participants attempted to quit smoking. Reports of cigarette consumption were assessed for the entire sample (N = 381) and for the subset of nonabstinent participants (n = 129 smokers). The results revealed high correlations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 30 publications
(45 reference statements)
3
53
0
Order By: Relevance
“…12 Interactive voice responses have been validated in comparison to those obtained through standard techniques. [17][18][19][20][23][24][25] When it comes to gathering sensitive information, these technologies have the added benefit of enhancing rates of disclosure. These investigations have shown that telephone interviews are at least as accurate as in-person interviews.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Interactive voice responses have been validated in comparison to those obtained through standard techniques. [17][18][19][20][23][24][25] When it comes to gathering sensitive information, these technologies have the added benefit of enhancing rates of disclosure. These investigations have shown that telephone interviews are at least as accurate as in-person interviews.…”
Section: Discussionmentioning
confidence: 99%
“…This technology has demonstrated promise in obtaining sensitive information from adults and adolescents. [17][18][19][20][21][22][23][24][25] IVR also has the potential to decrease the work burden on research staff, offer subjects enhanced confidentiality, and most importantly, allow subjects to initiate the contact within their own busy schedules rather than on the researchers' schedules.…”
mentioning
confidence: 99%
“…Toll, Cooney, McKee, and O'Malley (2005) investigated cigarette usage reported via IVR and compared this data to a timeline follow-back method (TLFB) where a thorough history of smoking history was recorded for the previous month. The TLFB method utilizes a calendar, in which participants record usage over a predefined interval.…”
Section: Accuracymentioning
confidence: 99%
“…Participants were instructed to take a lozenge every 2 hours as needed, and were maintained on the same strength of nicotine lozenge throughout their participation in the study (other than two participants who had the dosage increased from 2 to 4 mg due to breakthrough craving). Participants met weekly with a study physician (ALB or TZ) for 15-minute medication management visits, which consisted of assessment of adherence to the medication regimen, monitoring of smoking behavior, [59][60][61] and evaluation of side effects.…”
Section: Study Treatmentsmentioning
confidence: 99%